2018
DOI: 10.1002/ejsp.2518
|View full text |Cite
|
Sign up to set email alerts
|

Not all positive categories are alike: Exploring the superiority of the self as a positive source for associative attitude change via intersecting regularities

Abstract: In associative evaluative learning, attitudes can originate from intersecting regularities between a target and both positive‐ and self‐related stimuli. Liking for a focal target is primarily driven by its reference to one source, but it might be qualified by the reference to a contrast target. This contribution focuses on how the nature of positive and contrast sources affects learning via intersecting regularities. In two studies (N = 199 and N = 185), the self and another positive category lead to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Future research should test more directly the key role of this specific feature of the SR task in producing lasting changes in automatic evaluations towards food stimuli. For instance, as past studies demonstrated the role of individuals' self-esteem in moderating the SR effect (Mattavelli, Richetin, & Perugini, 2019;Prestwich et al, 2010), future studies could investigate the role played by this variable when the SR effect is tested over time.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should test more directly the key role of this specific feature of the SR task in producing lasting changes in automatic evaluations towards food stimuli. For instance, as past studies demonstrated the role of individuals' self-esteem in moderating the SR effect (Mattavelli, Richetin, & Perugini, 2019;Prestwich et al, 2010), future studies could investigate the role played by this variable when the SR effect is tested over time.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating this idea, Prestwich and colleagues (2010) showed that the higher the self-esteem, the larger the SR effect on implicit (but not explicit) evaluative change. Also, Mattavelli, Richetin, and Perugini (2019) observed, in a modified form of the SR task in which the self was opposed to an equally valenced attitudinal source, that the more positive the endorsed explicit self-view, the stronger the SR effect was. Thus, both implicit and explicit self-evaluations seem important qualifiers of the SR effect.…”
Section: Introductionmentioning
confidence: 94%